A new species of the putatively myrmecophilous genus Plaumanniola Costa Lima, with notes on the systematic position of Plaumanniolini (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
The enigmatic Neotropical genus Plaumanniola Costa Lima is revised. Plaumanniola sanctaecatharinae is redescribed and P. regina sp. n. is described (both from Brazil). Morphological structures of Plaumanniola are illustrated and the sys-tematic position of the tribe Plaumanniolini is discussed. A previously postulated myrmecophily of this morphologically highly unusual genus is found to be weakly supported by biological observations and should be treated as a supposition that needs further study.